A historical sensibility : Sir Michael Howard and the International Institute for Strategic Studies, 1958-2019. - Howard, Michael, 1922- (London : Routledge, 2020)
With the death of Professor Sir Michael Howard, The International Institute for Strategic Studies (IISS) lost not only its president emeritus but the last of its founders and intellectual parents. The foremost military historian of his generation, Sir Michael embodied and epitomised a historical sensibility that informed all his writing. He will forever remain an icon not only for historians, but for all those who acknowledge the indispensability of history and the historical sensibility for any true understanding of present events. In tribute to Sir Michael and in celebration of his life and work, this Adelphi book collects a selection of his remarks and writings for IISS publications over six decades, as well as previously unprinted material. Through this collection, these works will reach a new generation of readers and be made more accessible to those fortunate enough to have read them already. They illustrate Sir Michael's role in the Institute's creation and his abiding presence in its evolving intellectual life, and serve as a historical document, tracing the development of strategic thought and preoccupations from the 1950s to the recent past. In addition to their historical value, Sir Michael's conclusions retain their immediacy and power. This book is therefore of direct relevance to anyone interested in contemporary events: whether the professional analyst, the student of international relations or the general reader.
Introduction. John Chipman CMG, 'Professor Sir Michael Eliot Howard OM CH CBE MC FBA FRHistS: a tribute' 1. An interview with Sir Michael Howard 2. Present at the Creation 3. Book Reviews: Sociology and the military establishment 4. Book Reviews: Deterrence Or Defence 5.Book Reviews: Helmut Schmidt, Verteidigung oder Vergeltung 6.Letter to the Editor 7.Book Reviews: Beaufre and Aron books 8.Book Reviews: Deterrence Before Hiroshima: The Airpower Background of Modern Strategy 9. Book Reviews: Neither Liberty nor Safety: A Hard Look at US Military Policy and Strategy 10. Israel and the Arab World: The Crisis of 1967 11. The Classical Strategists 12. Obituary: B.H.L.H. 1895-1970 13. Book Reviews: The Roots of War: The Men and Institutions Behind US Foreign Policy 14.Obituary: P. M. S. Blackett 15. Order and Conflict at Sea in the 1980s 16.Letter to the Editor 17. Book Reviews: Offense and Defense in the International System 18. Obituary: Sir John Slessor Marshall of the Royal Air Force 19. Deterrence, Consensus and Reassurance in the Defence of Europe 20. Obituary: Raymond Aron 1905-1983 21. In memoriam: Hedley Bull 1932-1985 22. IISS - The First Thirty Years: A General Overview 23. The remaking of Europe 24.Brodie, Wohlstetter and American nuclear strategy 25. Old Conflicts and New Disorders 26. Lessons of the Cold War 27. When Are Wars Decisive? 28.Are We At War? 29. Review Essay: History, Tragedy and Farce
OCLC-licensed vendor bibliographic record.
Keywords: International Institute for Strategic Studies; Military history; Strategy; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Political Freedom & Security / General; POLITICAL SCIENCE / International Relations / General